BEHAVIOR OF MADRASAH HEADS IN CREATING AN EFFECTIVE MADRASAH CULTURE - Asrop Safi'i (Ta'allum: Jurnal Pendidikan Islam, 2023)
Madrasah principals play an important role in creating an effective madrasah culture. This research analyzed the behavior of the madrasah head in fostering an effective culture in human resources and services in the institution he leads. The research was conducted in 9 madrasah in Tulungagung Regency. Data was obtained through interviews and observation techniques. The research results show that efforts to create an effective madarasah culture are carried out through an adaptive and visionary leadership style. These include delegating tasks proportionally, having effective communication skills, being able to foster motivation in subordinates, and exercising measurable control. This research shows how a madrasah head has a big influence in fostering an effective work culture, if he can optimize the potential and he has power.